(untitled) (Physical Education, Health and Social Sciences, 2025)
1. Background and Study Aim The rapid integration of video-conferencing platforms into secondary education has generated concern regarding “Zoom fatigue” a technology-induced state of cognitive, emotional, and physical exhaustion. Adolescents, who possess heightened vulnerability to attentional overload and digital stress, remain underrepresented in empirical investigations. This study aimed to estimate the prevalence of Zoom fatigue among adolescents, identify its socio-demographic and behavioral predictors, and assess its association with cognitive load within digitally intensive learning environments. 2. Material and Methods A cross-sectional survey was administered to 742 adolescents aged 13–18 years recruited through stratified random sampling from public and private schools. Instruments included the Zoom Exhaustion and Fatigue Scale (ZEF), NASA-TLX cognitive load scale, and a socio-demographic and screen-behavior questionnaire. Data were collected through encrypted online forms. Analyses conducted using SPSS 29 included descriptive statistics, chi-square tests, Pearson correlations, and multivariable linear regression. Reliability was assessed using Cronbach’s alpha, and validity was supported through pilot-testing and factor analysis. 3. Results Overall, 61.7% of participants reported moderate-to-high Zoom fatigue. Cognitive load demonstrated a strong positive correlation with Zoom fatigue (r = .58, p < .001). Regression analyses revealed that female gender (β = .21), daily screen-time (β = .27), low socioeconomic status (β = .15), and multitasking behavior (β = .19) significantly predicted fatigue after adjusting for age and prior mental-health history. Instrument reliability values exceeded .88. 4. Conclusion Zoom fatigue is highly prevalent among adolescents and significantly associated with increased cognitive load. Socioeconomic and behavioral predictors underscore the need for policy-level reforms, including regulated screen-time, digital-pedagogy training, equitable technological access, and cognitive-load–sensitive instructional design.